The impact of photomindset media on students’ metacognitive awareness and reading comprehension - Nadia Putri Yudani; Sulastri Manurung; Safnidar Siahaan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study investigates the effects of photomindset media on students’ metacognitive awareness and reading comprehension. Employing a sequential explanatory mixed-methods design, the research involved 33 seventh-grade students at a junior high school in Batam. Quantitative data were collected using reading comprehension tests and the Metacognitive Awareness Inventory (MAI) developed by Schraw and Dennison, administered before and after the intervention. The photomindset media required students to observe images and respond to guided questions during reading activities. A paired-sample t-test was used to examine changes in students’ scores. To complement the quantitative findings, qualitative data were gathered through semi-structured interviews exploring students’ perceptions of the intervention. The results indicated significant improvements in both metacognitive awareness and reading comprehension. Students demonstrated enhanced planning, self-monitoring, and engagement while reading. Interview data further revealed that photomindset media supported visualization and deeper understanding of key textual details. Overall, the findings suggest that photomindset media serve as an effective and practical instructional approach for improving reading comprehension in EFL classrooms.